Architecture, remodeling, and functions of the septin cytoskeleton. Issue 1 (2nd August 2018) - Marquardt, Joseph; Chen, Xi; Bi, Erfei
Abstract: The septin family of proteins has fascinated cell biologists for decades due to the elaborate architecture they adopt in different eukaryotic cells. Whether they exist as rings, collars, or gauzes in different cell types and at different times in the cell cycle illustrates a complex series of regulation in structure. While the organization of different septin structures at the cortex of different cell types during the cell cycle has been described to various degrees, the exact structure and regulation at the filament level are still largely unknown. Recent advances in fluorescent and electron microscopy, as well as work in septin biochemistry, have allowed new insights into the aspects of septin architecture, remodeling, and function in many cell types. This mini‐review highlights many of the recent findings with an emphasis on the budding yeast model.